The Role of Organizational Commitments Mediates The Effect of Competence on Employee Performance in PT. Bali Tangi Spa Production - I Ketut Suantara; Ni Wayan Sitiari; Putu Ngurah Suyatna Yasa (Universitas Warmadewa, 2020)
Business development and competition will continue to increase from time to time following the development of information technology, so each company must continue to be creative and innovate by continuously improving the quality of its human resources. Human resources are one of the most important assets in a company or organization, as sophisticated and as complete as any other aspect of the organization but without the support of competent human resources, the organization will not operate well. This study aims to examine the effect of competence on employee performance, the effect of competence on organizational commitment, the effect of organizational commitment on employee performance and the role of organizational commitment mediating competence on employee performance. The method of determining the sample in this study uses a census method in which all employees totaling 37 people are sampled at PT. Bali Tangi Spa Production, Denpasar, Bali and data processing using Partial Least Square (PLS) analysis technique version 2.0. The results of the study stated that competence had a positive and significant effect on organizational commitment, competence had a positive and not significant effect on employee performance, organizational commitment had a positive and significant effect on employee performance and company commitment played a partial mediation in mediating competence on employee performance. In general, employees have a very good performance but management is advised to provide training, especially in the use of work equipment and also provide deeper motivation to increase organizational commitment.